Specific Features of Mitochondrial Dysfunction under Conditions of Ferroptosis Induced by t-Butylhydroperoxide and Iron: Protective Role of the Inhibitors of Lipid Peroxidation and Mitochondrial Permeability Transition Pore Opening - Tatiana Fedotcheva; Nikolai Shimanovsky; Nadezhda Fedotcheva (Membranes, 2023)
Recent studies have indicated the critical importance of mitochondria in the induction and progression of ferroptosis. There is evidence indicating that tert-butyl hydroperoxide (TBH), a lipid-soluble organic peroxide, is capable of inducing ferroptosis-type cell death. We investigated the effect of TBH on the induction of nonspecific membrane permeability measured by mitochondrial swelling and on oxidative phosphorylation and NADH oxidation assessed by NADH fluo rescence. TBH and iron, as well as their combinations, induced, with a respective decrease in the lag phase, the swelling of mitochondria, inhibited oxidative phosphorylation and stimulated NADH oxidation. The lipid radical scavenger butylhydroxytoluene (BHT), the inhibitor of mitochondrial phospholipase iPLA2γ bromoenol lactone (BEL), and the inhibitor of the mitochondrial permeability transition pore (MPTP) opening cyclosporine A (CsA) were equally effective in protecting these mitochondrial functions. The radical-trapping antioxidant ferrostatin-1, a known indicator of ferroptotic alteration, restricted the swelling but was less effective than BHT. ADP and oligomycin significantly decelerated iron- and TBH-induced swelling, confirming the involvement of MPTP opening in mitochondrial dysfunction. Thus, our data showed the participation of phospholipase activation, lipid peroxidation, and the MPTP opening in the mitochondria-dependent ferroptosis. Presumably, their involvement took place at different stages of membrane damage initiated by ferroptotic stimuli.